2011
DOI: 10.1093/nar/gkr765
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of an eIF3 subcomplex reveals conserved interactions required for a stable and proper translation pre-initiation complex assembly

Abstract: Translation initiation factor eIF3 acts as the key orchestrator of the canonical initiation pathway in eukaryotes, yet its structure is greatly unexplored. We report the 2.2 Å resolution crystal structure of the complex between the yeast seven-bladed β-propeller eIF3i/TIF34 and a C-terminal α-helix of eIF3b/PRT1, which reveals universally conserved interactions. Mutating these interactions displays severe growth defects and eliminates association of eIF3i/TIF34 and strikingly also eIF3g/TIF35 with eIF3 and 40S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
125
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(139 citation statements)
references
References 64 publications
14
125
0
Order By: Relevance
“…Subjecting Prt1 181C -Tif34-Tif35 to the limited proteolysis abolished the binding of Prt1 to the other two proteins by removing its C-terminal region. This confirms previous observations on the importance of the C-terminal region of Prt1 for binding to Tif34 and Tif35 Valasek et al 2001b, Herrmannova et al 2011. Further analysis of the binary interactions between these three proteins showed that the interaction between Tif35 and Prt1 is weak and sensitive to the salt concentration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Subjecting Prt1 181C -Tif34-Tif35 to the limited proteolysis abolished the binding of Prt1 to the other two proteins by removing its C-terminal region. This confirms previous observations on the importance of the C-terminal region of Prt1 for binding to Tif34 and Tif35 Valasek et al 2001b, Herrmannova et al 2011. Further analysis of the binary interactions between these three proteins showed that the interaction between Tif35 and Prt1 is weak and sensitive to the salt concentration.…”
Section: Discussionsupporting
confidence: 90%
“…5A). This is consistent with recent observations indicating that binding of Tif34 to Prt1 markedly stabilizes Tif35 association with the complex (Herrmannova et al 2011). Thermodynamic analysis of the interaction of Tif34 with Tif35 and Prt1…”
Section: Tif34 Bridges the Interaction Between Tif35 And The C-terminsupporting
confidence: 92%
See 1 more Smart Citation
“…eIF3, the largest eIF complex, is composed of 13 subunits, named eIF3a to eIF3m (30). Several of them have been identified as core subunits (47). eIF3b is one of them, whereas the others are eIF3j, eIF3a, eIF3g, eIF3i, and eIF3e (25,48).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the eIF3b WD40 domain interacts with the 40 S ribosomal subunit (57). This domain is followed by the C-terminal domain, necessary for the interaction with subunits eIF3i and eIF3g (47,66). Mutational analysis suggests that P311 binding to eIF3b involves the RRM.…”
Section: Discussionmentioning
confidence: 99%